LGG-32. Integrated biologic, radiologic and clinical analysis of pediatric low-grade gliomas during and after targeted therapy treatment. (3rd June 2022) - Tsai, Jessica W; Choi, Jungwhan John; Ouaalam, Hakim; Murrillo, Efrain Aguilar; Yeo, Kee Kiat; Vogelzang, Jayne; Sousa, Cecilia; Woods, Jared K; Ligon, Keith L; Warfield, Simon K; Bandopadhayay, Pratiti; Cooney, Tabitha M
Abstract: BACKGROUND: Pediatric low grade gliomas (pLGGs) are the most common central nervous system tumor in children, characterized by driver alterations in the RAS and MAPK pathways. Genomic advances have facilitated use of molecular targeted therapies, however their long-term impact on tumor behavior remains critically unanswered. METHODS : We performed an IRB-approved, retrospective chart and imaging review of pLGGs treated with off-label targeted therapy at Dana-Farber/Boston Children's Cancer and Blood Disorders Center from 2010 to 2020. Volumetric analysis was performed for BRAFV600E and BRAF fusion/duplication driven pLGG subsets. RESULTS : Fifty-five patients were identified (dabrafenib n = 15, everolimus n = 26, trametinib n = 11, and vemurafenib n = 3). Targeted agent was used as first or second-line therapy for 58% (32/55). Median duration of targeted therapy was 0.79 years (0.01 – 4.87), and overall median follow-up was 2.50 years (0.01 – 7.39). The 1-year, 3-year, and 5-year EFS from targeted therapy initiation were 62.1%, 38.2%, and 31.8%, respectively. Mean volumetric change for BRAFV600E mutated pLGG on BRAF inhibitors was -54.11%, and median time to best volumetric response was 8.28 months (n = 12). Median time to largest volume post-treatment was 2.86 months. Mean volumetric change for BRAF fusion/duplication pLGG on MEK inhibitors was +7.34% with median time to best volumetric response of 6.71 months (n = 7). Median time to largest volume post-treatment was 2.38 months. CONCLUSIONS : Our integrated clinical and volumetric data suggest the majority of patients receiving BRAF inhibitors or trametinib achieve reduction in tumor volume while on therapy and that tumor stability can be achieved following targeted therapy cessation. Moreover, volumetric analysis shows promise as a tool to assess targeted therapeutic response in pLGGs.